Comparative Analysis of Outcomes and Costs Following Open Radical Cystectomy Versus Robot-Assisted Laparoscopic Radical Cystectomy: Results From the US Nationwide Inpatient Sample - Yu, Hua-yin; Hevelone, Nathanael D.; Lipsitz, Stuart R.; Kowalczyk, Keith J.; Nguyen, Paul L.; Choueiri, Toni K.; Kibel, Adam S.; Hu, Jim C. (European urology, 2012)
Although robot-assisted laparoscopic radical cystectomy (RARC) was first reported in 2003 and has gained popularity, comparisons with open radical cystectomy (ORC) are limited to reports from high-volume referral centers. To compare population-based perioperative outcomes and costs of ORC and RARC. A retrospective observational cohort study using the US Nationwide Inpatient Sample to characterize 2009 RARC compared with ORC use and outcomes. Propensity score methods were used to compare inpatient morbidity and mortality, lengths of stay, and costs. We identified 1444 ORCs and 224 RARCs. Women were less likely to undergo RARC than ORC (9.8% compared with 15.5%, p=0.048), and 95.7% of RARCs and 73.9% of ORCs were performed at teaching hospitals (p<0.001). In adjusted analyses, subjects undergoing RARC compared with ORC experienced fewer inpatient complications (49.1% and 63.8%, p=0.035) and fewer deaths (0% and 2.5%, p<0.001). RARC compared with ORC was associated with lower parenteral nutrition use (6.4% and 13.3%, p=0.046); however, there was no difference in length of stay. RARC compared with ORC was $3797 more costly (p=0.023). Limitations include retrospective design, absence of tumor characteristics, and lack of outcomes beyond hospital discharge. RARC is associated with lower parenteral nutrition use and fewer inpatient complications and deaths. However, lengths of stay are similar, and the robotic approach is significantly more costly. Robot-assisted laparoscopic radical cystectomy is associated with lower parenteral nutrition use and fewer inpatient complications and deaths compared with open radical cystectomy. However, there was no difference in length of stay, and the robotic approach was significantly more costly.